PHOTODEGRADATION METHYLENE BLUE HYDROGELS USING ALCOHOL WITH POL IVINÍLICO TiO2 NANOPARTICLES - Carhuapoma, Wilson (2008)
A composite containing TiO2 nanoparticles immobilized in a polyvinyl alcohol (PVA) matrix, which was partially crosslinked by gamma radiation, was prepared. The colloidal suspension of TiO2 introduced in the polymeric matrix was characterized by UV-VIS, transmission electronic microscopy and X ray diffraction (XDR), whereas the composite PVA-TiO2 was characterized by UV-VIS and XRD. The efficiency of this material in photocatalysis has been evaluated against methylene blue. A fast fotodegradation of the dyestuff has been observed in different pH values.